Usage of wheat as an ingredient - Mumbai Archive Project Team (Jio Institute, 2024)
Wheat is the only ingredient that is not a spice. It helps thicken the curry that the masala is used to cook. Some households might choose to use chana dal instead of wheat. Similar to the preparation of the spices, the dal is also dried and roasted.